The aesthetic of the digital poem: Learn in poem get out of the humming of the hull by AbdelMoneim AlAzraq - Boumali, Hanane; Ayach, Souad (Milev Journal of Research and Studies, 2018)
This study seeks to explain how the poet Abdel-Moneim Al-Azraquses digitization techniques to convey the poetic content to be expressein his poem " get out of the humming of the hull ", which is part of thedigital literature that created its own characteristics. During this study,the mechanisms adopted by the poet to convey the poetic meaning and to clarify his vision of non-existence. We studied the reading language(visual language formation), the visual image (image formation, colorand camel movement) and audio music. Among them and fused into Bohe poet adopted the technique of multimedia to express his sense loss in his material world. As the paper poem passed through theadoption of the spoken language, the digital poem passed through the adoption of digitization techniques, and each of the two types had theirown circumstances.